STUDENTS’ PERCEPTION OF THE USE OF DUOLINGO APPLICATION IN LEARNING GRAMMAR - Rezikna; Nadrun, Nadrun; Wahyudin, Wahyudin; Mukrim, Mukrim (e-Journal of ELTS (English Language Teaching Society), 2023)
This research aims to find out students' perceptions on the use of Duolingo Application in learning grammar as an alternative media to students of SMA Negeri 1 Sindue Tombusabora. The subjects of this research were 26 tenth grade students of X MIPA1 SMA Negeri 1 Sindue Tombusabora. This type of research is a qualitative research method that describes the results of using Duolingo Application. The instruments used to collect data were interviews and questionnaires. The results of the data analysis show that the use of Duolingo Application in learning grammar has a positive perceptions on students. The results are also strengthened by the students’ perceptions that Duolingo Application was very positive for grammar learning. It can help the students learn about sentence structure, simple tenses, word class, and more. Most students responded that Duolingo Application motivated them to write sentences. The results of this research can be concluded that Duolingo Application has a positive effect on students in learning grammar.